1997
DOI: 10.1200/jco.1997.15.10.3249
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of newer prognostic markers for adult soft tissue sarcomas.

Abstract: P-gp expression, high-level Ki-67 expression, and nondiploid DNA content are independent prognostic indicators that correlate with poor outcomes in STS patients. However, MDR-1 mRNA was not found to be predictive of survival. These newer markers are useful additions to AJCC staging for prognostication for patients with STS. Such markers may be useful in selecting high-risk STS patients who could benefit from systemic adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 52 publications
3
25
1
Order By: Relevance
“…8,[20][21][22] Levine et al reported that high-level Ki-67 expression was an independent prognostic indicator that correlated with a poor outcome in patients with sarcoma. 10 Similar conclusions were reached in other studies. [23][24][25][26][27][28][29][30] Musella et al demonstrated that cyclin D1 overexpression was an independent factor for survival in patients with sarcoma, 11 and their results were confirmed in other reports.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…8,[20][21][22] Levine et al reported that high-level Ki-67 expression was an independent prognostic indicator that correlated with a poor outcome in patients with sarcoma. 10 Similar conclusions were reached in other studies. [23][24][25][26][27][28][29][30] Musella et al demonstrated that cyclin D1 overexpression was an independent factor for survival in patients with sarcoma, 11 and their results were confirmed in other reports.…”
Section: Discussionsupporting
confidence: 86%
“…Among these, p53 and proliferation markers, including PCNA, Ki-67 (MIB-1), and cyclin D1, have been investigated. [8][9][10][11] These 3 proliferation markers and p53 were chosen for use in the current study on the basis of their previous application in sarcomas and the underlying cell biology of these markers.…”
mentioning
confidence: 99%
“…We found PgP staining (>25%) in 40% of MFH and in 19% in mixed STS (with 6/18 MFH in the latter series having high Pgp expression) (Table 13), which is in line with reports from other authors who have reported Pgp expression in >50% of MFH and in varying frequencies in other STS entities [97,102,121]. We could not detect any prognostic importance of Pgp in the MFH series, whereas it was a strong prognostic factor for metastasis in the mixed STS series (Table 15).…”
Section: Pgpsupporting
confidence: 82%
“…In a meta-analysis of 27 studies including 631 patients with osteosarcoma, Pakos and Ioannidis [133] demonstrated that Pgp was not associated with histological response to chemotherapy, but was a strong prognostic factor for disease relapse and progression. In STS, Pgp expression has been suggested as a marker for poor sensitivity to chemotherapy and worse survival [81,102]. In rhabdomyosarcoma (RMS), Komdeur et al [95] showed that pediatric tumors differ from adult tumors in the expression of multidrug resistance associated proteins.…”
Section: Pgpmentioning
confidence: 99%
“…The expression of MDR proteins in soft tissue sarcoma has been correlated with a worse survival rate (24) or with a higher histologic grade (25). Leiomyosarcomas have been shown to have a weaker response to chemotherapy compared with other histologic types of sarcoma (26).…”
Section: Discussionmentioning
confidence: 99%